The Nexus Between Johannesburg Stock Exchange and the United States Unemployment Rate Announcement: An Impulse Response Analysis - Mutize, Misheck; Mugobo, Victor Virimai (Journal of Economics and Behavioral Studies, 2018)
The study explores the relationship between the unemployment rate in the United States and South Africa’s stock prices from the beginning of 2013 to the last day 2017. The objective of this paper is to examine the impact of the US unemployment rate announcement on the South African financial market. Results of Impulse Response analysis show that there is a very minimal impact from the US unemployment announcement to South Africa’s stock prices which disappears within two days of the announcement. In addition, the Johannesburg stock exchange index marginally responds to own shocks, which marginally fades away within two days. These findings imply that the changes in the US employment policies have a direct ripple effect on the South African macroeconomic environment, its investing public sentiments and corporate confidence on the future prospects of businesses.